MULTIMODAL IMAGING CHARACTERISTICS AND FUNCTIONAL CORRELATES IN RIP HEALING. Issue 10 (October 2022) - Romano, Francesco; Zicarelli, Federico; Cozzi, Mariano; Bertoni, Alice Ingrid; Cereda, Matteo Giuseppe; Bottoni, Ferdinando; Staurenghi, Giovanni; Invernizzi, Alessandro
Abstract : Supplemental Digital Content is Available in the Text. Macular areas with signs of tissue healing after retinal pigment epithelium tears secondary to neovascular age-related macular degeneration disclose better retinal sensitivity in case of improved blue-light and near-infrared autofluorescence signal and in the absence of fibrotic tissue. Abstract : Purpose: To report the imaging and functional features of the repair tissue following retinal pigment epithelium (RPE) tears. Methods: This cross-sectional observational study included patients with RPE tears secondary to neovascular age-related macular degeneration and at least 12 months of follow-up. The following variables were analyzed: best-corrected visual acuity; retinal sensitivity using microperimetry; outer retinal layers status and RPE resurfacing on optical coherence tomography; fibrosis; autofluorescence signal recovery using blue-light and near-infrared autofluorescence. Results: Overall, 48 eyes were included (age: 82 ± 5 years) and 34 of them showed signs of healing. Retinal pigment epithelium resurfacing was noticed in 22 cases, whereas fibrosis appeared in 21 eyes. Autofluorescence improved in 17 cases using blue-light infrared autofluorescence and 7 eyes on near-infrared autofluorescence. Outer retinal layers were more frequently preserved when RPE resurfacing and autofluorescence improvement occurred ( P < 0.05). Although best-corrected visual acuity was higher for smaller RPE tears ( P = 0.01), retinal sensitivity of the healing tissue was positively affected by autofluorescence improvement ( P < 0.001) and by absence of fibrosis ( P = 0.03). Conclusion: Autofluorescence signal recovery after rip occurrence possibly reflects the underlying status of the RPE and is associated with better functional outcomes. Our findings highlight the importance of blue-light infrared autofluorescence and especially near-infrared autofluorescence assessment in the setting of rip healing.